Dimensões formativas nos tempos educativos da pedagogia da alternância: um estudo a partir do pensamento de Anton Makarenko - Oliveira, Fábio Silva de (2021)
This research investigated the formative dimensions in the educational times of Pedagogy of Alternating present in the Project of the Projeto do Curso Técnico Integrado em Agropecuária do Instituto Federal Catarinense (IFC) - Campus Avançado de Abelardo Luz, through the Soviet pedagogue Anton Semiónovitch Makarenko’s (1888-1939) thinking. The methodology, the pedagogical praxis and the conceptual dimensions that he forged during his experiences in the educational colonies where he taught were evaluated, such as the concept of discipline, collectivity, self-organization and socialization of man through collective work. The study problematized discussions turned to the field of the curriculum, in this case, the educational times in the Pedagogy of Alternating - central theme of the study. The research scenario was the integrated technical high school of the IFC - Campus Avançado de Abelardo Luz and the instruments used for the analysis unfolding were the Projeto de Curso Técnico Integrado em Agropecuária and the documents that found the technical course in research. The justification of the present work was given by the social and academic relevance when thinking about the specificities offered by the course to students who live in the countryside, as the main teaching environment of the research is located in a rural settlement area. This was a qualitative analysis and the methodology used was the conceptual theoretical analysis, under the categories extracted from Makarenko's pedagogy. The reflections were made based on the theoretical framework of some leading authors in the field of study, such as Pessoti (1978), Begnami (2003), Caldart (2010), Gimonet (2007), Silva (2012), Freire (1987), Gadotti (2003), Santos (2010), Ramos (2010), Ciavatta (2014). The conceptual theoretical analysis was based on the thought of Makarenko and, after compiling the categories of analysis, focused on documents related to the Curso de Ensino Médio, Técnico e Profissionalizante em Agropecuária do IFC - Campus Avançado de Abelardo Luz to understand the structuring of the formative dimensions within the educational times of an alternating curriculum. The analysis showed, in its totality, the importance of the foundation of federal institutes for integrated training between high school and professional education, under an integrative humanizing teaching perspective, made for and by the collective, seeking the students' autonomy. Looking specifically at the scope of the communities living in and in the countryside, there was an urgent need for professional education allocated within the rural settlement, guaranteeing them the same education rights. It was concluded that Pedagogy of Alternating became a curricular reality for the Course hereby studied, because, in this scope, learning and knowing are not obtained through the formal logic of acquisition or accumulation of knowledge, but involve a dialogical, non-hierarchical process, based on reciprocal relationships between educator, student and their reality. The pedagogical planning of this education proved to be the main pedagogical challenge for the development of this proposition. The alternation of educational times organized by themes experienced in the students’ daily lives appeared as a point of balance in the promotion of this comprehensive education.